Expert Consensus for Treating Cancer Patients During the Pandemic of SARS-CoV-2 - Dong, Shuang; Luo, Chenggang; Hu, Xuebo; Zhang, Jing; Cai, Qian; Qian, Yu; Ran, Fengming; Ou, Wuling; Wang, Jun; Huang, Qing; Ren, Tianhua; Han, Guang; et al. (Frontiers in Oncology, 2020)
The sudden pandemic of SARS-Cov-2 (also known as novel coronavirus disease 2019, COVID-19) poses a severe threat to hundreds of millions of lives in the world. The complete cure of the virus largely relies on the immune system, which becomes particularly a challenge for the cancer subjects, whose immunity is generally compromised. However, in a constant evolving situation, the clinical data on the prevalence of SARS-Cov-2 for cancer patients is still limited. On top of a wide range of medical references and interim guidelines including CDC, NCI, ASCO, ESMO, NCCN, AACR, ESMO, and the National Health Commission of China, etc., we formed into a guideline based on our experience in our specialized cancer hospital in Wuhan, the originally endemic center of the virus. Furthermore, we formulated an expert consensus which was developed by all contributors from different disciplines after fully discussion based on our understanding and analysis of limited information of COVID-19. The consensus highlighted a multidisciplinary team diagnostic model with assessment of the balance between risks and benefits prior to treatment, individualizing satisfaction of patients’ medical needs, and acceptability in ethics and patients’ socio-economic conditions.